Alterations in virulence and antibiotic resistant genes of multidrug-resistant Salmonella serovars isolated from poultry: The bactericidal efficacy of Allium sativum. (July 2017) - Salem, W.M.; Shibat El-hamed, Dina M.W.; Sayed, W.F.; Elamary, R.B.
Graphical abstract: Highlights: 13 Salmonella serovars isolated and identified from diseased chickens. Virulence and antibiotic resistance genes were determined by PCR. The highest biofilm density observed in S. takoradi and S. Apeyeme . All isolates were multi-resistant against most of B -lactams groups. The efficiency of garlic extract was assessed ( in vitro and in vivo ).